Evaluation of usage of immunity boosters among the citizens of Pune district during the COVID-19 pandemic - Manjusha Sajith; Ritika Rajendra Danole; Jilu Treasa Shaji; Ansee Kuruvila (Wolters Kluwer Medknow Publications, 2023)
Introduction: Post the coronavirus disease (COVID-19 pandemic), there was a spike in demand for immunity boosters, leading to the irrational use of supplements. To assess the usage of immunity boosters among the citizens of Pune City and correlate the side effects associated with supplements. Material and Methods: A cross-sectional study was conducted from September 2020 to May 2021 in Pune. Data, such as demographic, supplement intake (allopathic, homeopathic, and ayurvedic/home remedies), duration, frequency of supplements, and side effects associated with supplements, were collected through a personal interview and e-form circulation. The correlation of the immunity boosters with the side effects was done using Karl Pearson's Correlation test in SPSS software version 22.0. Results: Out of 1006, the ayurvedic supplements/home remedies were preferred by 906 (98%) allopathic supplements by 599 (65%) and homeopathic supplements by 256 (28%) participants. The commonly reported side effects were acidity (37%), headache (29.6%), nausea (9%), loss of appetite (8.8%), diarrhea (7%), stomach ache (6%), cough (5.6%), and constipation (4.1%). These side effects had a weak positive linear proportionality with ayurvedic supplements such as amla (r = 0.162), Giloy Vati (r = 0.139), turmeric (r = 0.108), and Kadha (r = 0.102); also, Eupatorium perfoliatum, Vitamin C, and Vitamin D showed a linear proportionality with loss of appetite (r = 0.15), headache (r = 0.12), and cough (r = 0.12), respectively. A higher incidence of side effects such as nausea (r = 0.267), diarrhea (r = 0.243), headache (r = 0.164), and acidity (r = 0.113) was observed when supplements were taken for 6 months. Conclusion: Most participants were on immunity boosters during the COVID-19 pandemic. The study concluded that using immunity boosters in excess or for more than 6 months causes side effects, the most recurrent ones being acidity, headache, nausea, and lack of appetite.